Nursing assistance in patient safety in the intensive care unit (Research, Society and Development, 2024)
Since the publication of the document "To err is human: building a safer health care system," the theme of patient safety has begun to generate discussions worldwide. The study aims to evaluate the conduct of the nursing team in promoting patient safety in the intensive care unit. It is an integrative literature review, with a qualitative approach, conducted during May 2022. Data collection took place on the Virtual Health Library (VHL) portal, using the following descriptors: patient safety, nursing care, intensive care unit. The final sample consisted of 04 articles. The main conducts performed by the nursing team to promote patient safety can be observed, from the use of biosafety measures such as hand hygiene to the implementation of complex protocols and checklists, aiming to improve healthcare quality and minimize errors in the ICU. Although few studies were selected for evaluation, the conduct and care of the Nursing team in promoting patient safety can be observed. However, further discussions and studies on the topic are necessary.